Adaptation of Sport Brand Personality Scale to Turkish - İ, Görgüt; Özbal A.F. (Horizon Research Publishing Co., Ltd., 2018)
Validity and reliability of Turkish form of sport brand personality scale, which was developed by Mitsis and Leckie (2016), was presented in this study. Scale was designed to reflect the impact of individuals' favorite athletes on them in other words the strength of the role model factor. In study, participants were tried to reach through an online form on voluntary basis and participants were included into the study in two stages as pilot and main study. After the incorrect and incompletely filled scale forms had been taken out, 107 people were taken for the pilot study and 326 people were taken for the validity and reliability of the study, in total 433 people were taken into account for the statistical procedures. When the educational status of participants were asked in the study; it was stated that, 1 of participants was literate, 2 of participants were primary school, 6 of participants were secondary school, 69 of participants were high school, 300 of participants were university graduate and 55 of participants were undergraduate. When we look at age distribution of the participants, 10.6% of them were in 14-19 age group, 37.4% of them were in 20-25 age group, 20.6% of them were in 26-31 age group, 14.3% of them were in 32-37 age group, 9.5% of them were in 38-43 age group, 5.3% of them were in 44-49 age group, 2.1% of them were in 50-55 age group and .2% of them were in 56 age and above group. For the Turkish adaptation of scale, language validity was provided through expert opinion. Validity of scale was assessed with confirmatory factor analysis and reliability of scale was assessed with split-half reliability methods. For the six subscales, it was seen that fit indices were in acceptable level for X2/df, RMSEA, RFI, GFI, AGFI and in perfect level for CFI, NNFI, NFI, IFI. In conclusion, the internal consistency for all scale was .95 and for the six subscales respectively were .91, .86, .86, .84, .77 and .90. In conclusion, obtained data by the application of Turkish form of scale showed that adapted scale having six subscales, 19 items and 7 Likert type scoring tool, was a valid and reliable scale.
Keywords: Brand; Reliability; Personality; Scale; Sport; Validity; 4. Education; 10. No inequality; 16. Peace & justice